EVALUATION OF HAEMATOLOGICAL AND SERUM BIOCHEMICAL PROFILES OF XYLAZINE-KETAMINE INDUCED ANAESTHESIA IN QUAILS (COTURNIX COTURNIX) - Pallavi Upadhyay; M. Palanivelrajan; A. Senthilkumar; P. Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Effects of xylazine and ketamine on physiological, haematological and serum biochemical parameters in common quails (Coturnix coturnix) was assessed. Six healthy quails were given intramuscular injections of xylazine @ 9 mg/kg body weight and ketamine @ 30 mg/kg body weight. Blood samples were drawn from brachial vein both before and after anaesthesia from each bird. Data was collected for analyzing the change in physiological haematological and biochemical parameters were collected before, during and after anesthesia and were compared. The results showed that the induction period was (2.02±0.20 minutes) and duration of general anesthesia was (82.5 ±3.64 min). Haemoglobin (Hb) concentration, Packed cell volume (PCV), Red blood cell (RBC) count and Glucose level showed significant changes. It was concluded that administration of anaesthesia using xylazine and ketamine may alter some haematological and biochemical values.This should be considered when evaluating blood samples from chemically immobilized or sedated quails.